GENDER DISPARITY IN ICT COMPETENCY AMONG TEACHERS IN FEDERAL TERRITORY LABUAN, MALAYSIA. - Ambotang, Abdul Said (UPI Press, 2012)
ICT has today become a must-have tool in school. For this, government has spent a lot of resources to upgrade the ICT infrastructure both in primary and secondary schools.Â A lot of money has been spent to train teachers as well. With this investment, the government hopes that ICT can be fully utilized. However, ICT facilities can only be fully used if teachers are competent. This study was to assess the level of ICT competency among teachers in Federal Territory Labuan. In particular, it examined the differences between females and males in terms of nine components (MS WORD, MS POWER POINT, MS EXCEL, MS ACCESS, WWW, E-MAIL, OPERATING SYSTEM, MULTIMEDIA, and VIRTUAL CLASS application) related to ICT. A total of 256 teachers participated in this study. The results of the study showed that there is a small gap between females and males teachers. In some application such as MS WORD, MS POWER POINT, MS EXCEL, female teachers were more competent compared to male teachers. In contrast, male teachers are more capable in MS ACCESS,WWW, E-MAIL, OPERATING SYSTEM, MULTIMEDIA, and VIRTUAL CLASS application. Various reasons attribute to these results.Â Keywords: Gender Disparity, ICT Competency, Computer software